MANAJEMEN PEMBELAJARAN BERHITUNG ANGKA 1-10 MELALUI MEDIA TIKAR BILANGAN UNTUK MENINGKATKAN KECERDASAN BERPIKIR ANAK USIA DINI - Supriatin, Wiwin (PT. Solusi Komunikasi Terapan, 2023)
This research aims to get an overview of: planning, organizing, implementing, evaluating, obstacles and solutions in learning to count numbers 1-10. The approach taken is qualitative and the research method is descriptive method. Research techniques use observation, interviews and documentation studies. The results of this research are: the principal and teachers work together to create a numeracy learning program in planning the program to determine the goals to be achieved, selecting materials, methods and media outlined in the RPPH, organizing continues from planning, implementation of learning has gone well despite the results not yet optimal due to various things and obstacles. Learning evaluation is carried out to determine the extent to which children understand learning to count, the teacher has carried out an evaluation/assessment; daily, weekly, monthly and semester. The assessment carried out by the teacher is in the form of observations, recording anecdotes, work results, portfolios, performance. The obstacles are that active children tend to often disturb other children, children do not understand learning activities, learning media are less supportive, learning methods are not varied, human resources are inadequate. low quality, the number of teachers and students is not balanced, the principal and teachers have implemented various solutions by means of children who are active and do not understand the lessons in numeracy being near the teacher, alternating learning media, supervision of the principal, comparative studies, training and workshops on learning, recruiting accompanying teachers to help make learning in the classroom more conducive